Outdoor-to-Indoor Channel Measurement and Coverage Analysis for 5G Typical Spectrums - Zhimeng Zhong; Jianyao Zhao; Chao Li (International Journal of Antennas and Propagation)
The fifth-generation (5G) mobile communications system will adopt the millimeter wave (mmWave) band for outdoor-to-indoor (O2I) coverage to achieve ultrahigh data rate. However, it is a challenging task because of the large path loss and almost total blocking by building walls. In this work, we performed extensive measurements on the O2I propagation at 3.5, 4.9, and 28 GHz simultaneously by using a multiband channel sounder. We captured the path loss distribution and angular power arrival profiles. We also measured the penetration loss at 28 GHz through different kinds of glass windows. The widely adopted ordinary glass windows introduce the penetration loss of 3 to 12 dB that is acceptable and makes mmWave O2I coverage feasible. But the low-emissivity (low-E) windows that will be more popular in the future introduce 10 dB higher loss. The measurement results in this work can help analyse and anticipate the O2I coverage by mmWave, which is important for the design and deployment of the 5G network.